Hubungan antara minat baca dengan kemampuan berpikir kritis dalam pembelajaran IPS di sekolah dasar - Purbaningrum, Ainun Dyah; Siti Poerwanti, Jenny Indrastoeti; Widianto Atmojo, Idam Ragil (Universitas Sebelas Maret, 2024)
The research purpose was determined the correlation of reading interest and critical thinking ability in social studies learning at elementary school. This research type is a quantitative approach with correlational research design. The research sample was fifth grade students at SDN Laban 01, SDN Wirun 04, SDN Laban 02, and SDN Plumbon 02, Mojolaban District, Sukoharjo Regency. The sampling technique applies the probability sampling technique of cluster random sampling type. Data collection techniques for reading interest and critical thinking ability are in the form of tests and questionnaires. Analysis prerequisite test using normality and linearity tests. Hypothesis testing using simple correlation analysis by applying Pearson Product Moment correlation and multiple correlation analysis with the help of the SPSS 21 program. The results showed that reading interest affect critical thinking ability in fifth grade students of SD in Mojolaban District.